Insights in Specific Cerebellar and Cerebral Activations in Blind Subjects - Gizewski, Elke R.; Timmann, Dagmar; Forsting, Michael (Current Medical Imaging, 2006)
In the past, many aspects concerning specific cerebral activation patterns and cross-modal plasticity in blind subjects have been reported. Experimental data on cortical reorganization in blind subjects, using positron emission tomography (PET) and functional magnetic resonance imaging (fMRI), has revealed activation of the visual cortex related to Braille reading and tactile discrimination tasks in congenitally and early blind subjects. In addition to the cortical activity in sensorimotor and visual areas, an increased global activation of the cerebellum has been shown during Braille reading in blind subjects. Our studies addressed the two aspects mentioned above: early blind and normal sighted subjects were studied with fMRI during Braille reading, tactile discrimination of nonsense dots, sensory electrical stimulation and finger tapping to reveal specific cerebral and cerebellar activation and further insights into cross modal plasticity. Findings of specific cortical and cerebellar activation during Braille reading in normal volunteers and blind subjects are discussed in light of the current literature concerning cross modal plasticity and the hypothesis of cerebellar involvement in language processing.
Keywords: Blindness